Soft Skills: Types, Characteristics and Importance - Chaudhari, Tushar (Journal of Commerce and Trade, 2021)
In today's viable eco-sphere soft skills requisite upgrading. Delegate skills are the common skills which are required for attainment in any discipline of life. This paper is about soft skills concept, its types and characteristics. The said research is done entirely done on secondary data and conclusion and recommendations are drawn to help individual to master common skill. Main recommendations include to have protagonist model and rehears it. Reputation of people skill is huge, many time they became the basic reason for the success or failure of a candidate. This article studies the soft skill concept along with its characteristics and importance. The role model is key for development of soft skill. Any individual who has desire of developing soft skill need to observe the role model. Every now and then individual must be open for feedback. The objectives of the present study are to study awareness of concept of soft skill and its types; to analyses its characteristics; to check soft skill’s importance and to suggest the ways of conquering soft skill. Soft skills are vital in today's life. There are voluminous individuals who are willing to master this art. soft skills possess multiple advantages. To mature in common skill one need to practice and practice. Classification-JEL : J24